(untitled) (Research, Society and Development, 2024)
Cholecystectomy consists of surgery that results in the excision of the gallbladder. This study aimed to identify the clinical characteristics of patients undergoing cholecystectomy. Method: A scoping review was carried out, following the guidelines established by the Joanna Briggs Institute (JBI). Results: The results revealed that laparoscopic cholecystectomy is the most prevalent surgical technique. The predominant age range of patients undergoing this intervention is between 40-60 years old, with a higher prevalence in females. ASA I and ASA II scores were the most common. Frequently associated comorbidities include systemic arterial hypertension, diabetes mellitus, hypothyroidism, dyslipidemia, smoking, systemic heart disease and renal failure. Abdominal pain, especially in the right upper quadrant, was the most prevalent symptom, accompanied by nausea, dyspepsia, vomiting and a positive Murphy’s sign. Conclusion: This research highlighted the importance of analyzing the clinical profile of patients undergoing cholecystectomy, providing a comprehensive view in line with existing literature.